Inclusion of the Subject “Law and Literature” at UNAM: Legal Interdisciplinarity and Challenges - Mejía Hernández, Diana Osmara (Iuris Dictio, 2026)
Legal education in Mexico faces significant pedagogical and training challenges. Although educational practices aimed at moving beyond the legal positivist paradigm and incorporating interdisciplinary and critical approaches into the curriculum have been promoted in recent decades, these advances face structural limitations. This article aims to identify the shortcomings stemming from traditional legal education and demonstrate the relevance of interdisciplinarity as a current field in Mexican legal academia. In particular, it analyzes the incorporation of the course Law and Literature as an expression of this improvement and highlights its contribution to curricular strengthening and diversification in the UNAM. However, it examines the scope and challenges accompanying its implementation, particularly with regard to the limited openness to academic feminism as an emerging field of interdisciplinary studies and its limited methodological and epistemological output.